Acrostichum daneifolium - Edward F. Gilman (EDIS, 2004)
This beautiful fern (Figure 1) that is native to Florida grows larger than many other ferns, becoming 4 to 8 feet tall. The 3- to 6-foot-long, pinnately divided fronds emerge from the ground to form a beautifully textured, open form. The plant changes very little throughout the year, but provides a continual green mass of beautiful foliage. This document is Fact Sheet FPS-12, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: October 1999; reviewed October 2003.